PENGARUH KUALITAS LINGKUNGAN PERUMAHAN TERHADAP KESEHATAN DAN GIZI IBU HAMIL DI KOTA MEDAN (JURNAL ILMIAH KOHESI, 2022)
Poor environmental conditions also affect the nutrition of pregnant women, where an unfavorable environment will affect food sterility, where food that is safe for pregnant women to eat must be stored in an atmosphere that practices good environmental hygiene. Food can be contaminated by pathogenic germs such as bacteria, viruses, or parasites if the living space is unhygienic. These tainted foods can cause illness or food poisoning, which can harm the health of pregnant women and reduce nutrient absorption. Nutrition of pregnant women can be maintained by maintaining the cleanliness of the kitchen. In addition to preventing the growth of harmful germs, a clean and hygienic kitchen helps prevent cross-contamination between raw foods and ready meals. This study aims to find out what factors cause pregnant women and their children to experience growth and development disorders and mindset disorders while in their living environment, as well as interference in obtaining nutritional intake, in addition to what actions must be taken by the Medan City Government in order to prevent disturbances that occur, and what the Medan City Government does in terms of providing nutritional intake food that will have an impact on improving the quality and intelligence of children, as well as preventing disruption of mindset in children. This research uses a type of qualitative descriptive research. The results of the study stated that the environmental conditions in Medan City that make pregnant women in Medan City do not get maximum services about health by the Medan City Government, so that the Medan City Government must carry out prenatal care, safe childbirth, and postnatal care as part of maternal and child health initiatives, run a vaccination program that offers injections to children and pregnant women, Providing education to adolescents and pregnant women about reproductive health to help them understand the value of institutional care and make health services, such as hospitals, primary care clinics, and maternity and child health centers, more accessible and available in rural and remote locations, and to maintain their cleanliness and safety, the government monitors residential environments and water quality.